A Comparison of the Chemical Properties of Flours Made from Sweet and Bitter Varieties of Cassava in Guyana - Joseph, Samantha; Uzzi, Medeba; Dey, Basil (Discoveries in Agriculture and Food Sciences, 2025)
The use of cassava flour in flour composites and as a gluten-free alternative to wheat is on the increase. The Government of Guyana seeks to tap into this emerging market by increasing cassava flour production and exports however the absence of a regional standard for cassava flour limits exportation goals. Characteristics of prepared flours depend on cultivar type, geographical location, age of the plant and environmental conditions. This research sought to characterize cassava flours made from bitter and sweet varieties of the same age and sourced from the same geographical location. Flours were prepared from the roots of three sweet varieties; ALBS, Smokie and Yardie; and three bitter varieties; LPL67, GAA98 and WS13. The chemical characteristics observed were moisture, protein, starch, far, crude fiber, ash, residual cyanide and pH. There were no significant differences (p>0.05) in moisture, starch, crude fiber, ash and pH between bitter and sweet varieties. Differences were significant (p<0.05) for protein (bitter: 1.79%, sweet: 2.92%), fats (bitter: 2.32%, sweet: 1.62%) and cyanide (bitter: 84.24ppm, sweet: 12.41ppm). An inverse relationship (R = -0.667) existed between moisture and protein content for the sweet varieties. All flours prepared from the bitter varieties had residual cyanide levels in excess of the 10 mg/kg recommended by WHO. This preliminary data favors sweet varieties for cassava flour production and provides initial data for a local repository of cassava flour characteristics for use in generation of a local/regional standard.